2022
DOI: 10.3390/biomedicines10061375
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Quality Control in the Heart: The Balance between Physiological and Pathological Stress

Abstract: Alterations in mitochondrial function and morphology are critical adaptations to cardiovascular stress, working in concert in an attempt to restore organelle-level and cellular-level homeostasis. Processes that alter mitochondrial morphology include fission, fusion, mitophagy, and biogenesis, and these interact to maintain mitochondrial quality control. Not all cardiovascular stress is pathologic (e.g., ischemia, pressure overload, cardiotoxins), despite a wealth of studies to this effect. Physiological stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 101 publications
0
6
0
Order By: Relevance
“…Mitochondria are highly dynamic organelles. Appropriate management of mitochondrial biogenesis, fission/fusion, and mitophagy is essential for preserving mitochondrial integrity and function ( Fajardo et al, 2022 ). In our current work, we detected the expression of critical proteins in mitochondrial quality control using western blot analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondria are highly dynamic organelles. Appropriate management of mitochondrial biogenesis, fission/fusion, and mitophagy is essential for preserving mitochondrial integrity and function ( Fajardo et al, 2022 ). In our current work, we detected the expression of critical proteins in mitochondrial quality control using western blot analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Our data showed that at least the defective mitochondrial fusion and mitophagy partially mediated the impairment of mitochondria in cardiac muscles from patients with PD. The mitochondrial morphology, quality and abundance are recognized as being determined by the mitochondrial dynamics comprising mitochondrial fusion, fission, biogenesis and mitophagy 28 . Imbalanced or damaged mitochondrial dynamics have been implicated in the development and progression of cardiovascular pathologies 24,29 .…”
Section: Discussionmentioning
confidence: 99%
“…The mitochondrial morphology, quality and abundance are recognized as being determined by the mitochondrial dynamics comprising mitochondrial fusion, fission, biogenesis and mitophagy. 28 Imbalanced or damaged mitochondrial dynamics have been implicated in the development and progression of cardiovascular pathologies. 24 , 29 Mitochondrial fusion connects neighbouring depolarized mitochondria and mixes their contents to maintain membrane potential.…”
Section: Discussionmentioning
confidence: 99%
“…The expression analysis of genes involved in the regulation of mitochondria biogenesis and cell energetics, such as PGC1β (peroxisome-proliferator-activated receptor-γ-coactivator 1 β), TFAM (transcription factor A were greater in TgRRB hearts suggesting that there is greater OXPHOS gene expression [43,44] (Fig. S10).…”
Section: Tgrrb-cms Have Enhanced Mitochondrial Function Compared To W...mentioning
confidence: 99%